The Effect of Hypnosis in Reducing Antenatal Anxiety and Pain at Garuda Health Center (HEALTH CARE: JURNAL KESEHATAN, 2025)
Childbirth is a stressful event for most women in the labor process that can increase pain, fear and anxiety. To overcome anxiety and pain that are often experienced by pregnant women during pregnancy and childbirth, it can currently be reduced by using non-pharmacological methods. Hypnosis, which is a state of deep relaxation that allows someone to be more receptive to suggestions, has been shown to be effective in reducing anxiety levels and pain perception. This study aims to determine the effect of self-hypnosis on antenatal anxiety and pain. The population in this study were pregnant women in the Garuda Health Center work area. Samples were taken from 35 primigravida pregnant women. This study was analyzed using the Wilcoxon test. Antenatal anxiety and pain in respondents were measured using the Distress Scale and VAS. Respondents were given health education and self-hypnosis training after taking the pre-test. The post-test used the same instrument as the pre-test. The results of the analysis found a significant difference in anxiety and pain in respondents before and after hypnosis (p = 0.0005, d "0.05) meaning that there was a decrease in anxiety and pain in antenatal mothers after hypnosis. It is recommended for health workers in the community to increase comfort in pregnant women so that they are ready to face childbirth by using Hypnotherapy.